2021
DOI: 10.11622/smedj.2021051
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological patterns and survival outcomes of colorectal cancer among young adults in Malaysia: an institutional cohort study

Abstract: Introduction: This study aimed to investigate the clinicopathological patterns and survival outcomes of young-onset colorectal cancer (CRC) in Malaysia. Methods: The study consisted of 206 patients with young-onset CRC (age < 50 years at diagnosis) and 1,921 patients with late-onset CRC (age ≥ 50 years at diagnosis) diagnosed during 2002–2016. The clinicopathological characteristics of patients with young-onset CRC were compared with those of patients with late-onset CRC during 2009–2013. Kaplan-Meier survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…Several studies have shown poor survival outcomes due to a higher proportion of progressive tumours, 46 , 47 whereas others have reported a better prognosis than later‐onset patients. 40 , 42 , 48 However, previous studies have certain limitations, such as inconsistent definitions of EOCRC or LOCRC, 49 , 50 , 51 studies only on patients with progressive tumours, 52 , 53 and insufficient study inclusion for prognostic analysis (fewer than 100 cases), 17 , 54 which do not allow for the exposure of actual prognostic differences between the two age groups. Our study found no differences in 5‐year CSS, consistent with the results of several large‐scale retrospective studies in recent years, 20 , 55 and similar results were obtained for metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown poor survival outcomes due to a higher proportion of progressive tumours, 46 , 47 whereas others have reported a better prognosis than later‐onset patients. 40 , 42 , 48 However, previous studies have certain limitations, such as inconsistent definitions of EOCRC or LOCRC, 49 , 50 , 51 studies only on patients with progressive tumours, 52 , 53 and insufficient study inclusion for prognostic analysis (fewer than 100 cases), 17 , 54 which do not allow for the exposure of actual prognostic differences between the two age groups. Our study found no differences in 5‐year CSS, consistent with the results of several large‐scale retrospective studies in recent years, 20 , 55 and similar results were obtained for metastatic CRC.…”
Section: Discussionmentioning
confidence: 99%
“…There were 78 studies 12,13,18,[94][95][96][97][98][99][100][101][102][103][104][105][106][107][108] that reported on 17 signs and symptoms at presentation, based on claims or medical records (66 studies), 12, 13, 27, 28, 30, 32-34, 38-40, 42-45, 47, 48, 51-77, 79, 81, 83, 84, 86-92, 94-104 patient report (6 studies), 18,29,37,46,80,82 or other (7 studies). 31,35,41,49,50,78,85 (Figure 2; eFigure 1 in Supplement 1).…”
Section: Presenting Signs and Symptomsmentioning
confidence: 99%
“…The Duke’s stage or TNM staging, number of lymph nodes involved, distant metastases, pre and postoperative carcinoembryonic antigen (CEA) level, tumour grade and location are regarded as prognostic markers with utmost prognostic importance that predict the survival of individuals with colorectal cancer [ 7 , 8 ]. In colorectal cancer, the best prognosis estimate is based on the anatomic extent of illness as established by the pathological inspection of the resected specimen [ 9 ]. However, precise prognostic factor identification for colorectal cancer CRC still poses a challenge; thus, further research is required to understand the predictive relevance of clinicopathological factors in CRC, particularly for Malaysian records.…”
Section: Introductionmentioning
confidence: 99%